2014
DOI: 10.1684/ejd.2013.2214
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma attributable to sunbed use and tan seeking behaviours: an Italian survey

Abstract: Melanoma attributable to sunbed use and tan seeking behaviours: an Italian surveyMelanoma is the most deadly form of skin cancer and its incidence is increasing worldwide. In 2009, the International Agency for Research on Cancer classified the entire UV spectrum as carcinogenic. In many countries, including Italy, the use of tanning equipment by minors and individuals with high risk phenotypes has been banned. This study assessed tan-seeking behaviour in a Mediterranean population with a relatively high melano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 22 publications
1
17
0
4
Order By: Relevance
“…Second, the unintended sunburn group may have less positive attitudes towards tanning and may be more amenable to behavioural change to reduce the risk of future unintended sunburns [29, 30]. Third, the unintended sunburn group may have a pattern of high intermittent UV exposure as their sunburn may be a result of a lack of preparation for being outdoors [15, 31]; intense intermittent sun exposure is implicated in the development of melanoma [3234]. …”
Section: Introductionmentioning
confidence: 99%
“…Second, the unintended sunburn group may have less positive attitudes towards tanning and may be more amenable to behavioural change to reduce the risk of future unintended sunburns [29, 30]. Third, the unintended sunburn group may have a pattern of high intermittent UV exposure as their sunburn may be a result of a lack of preparation for being outdoors [15, 31]; intense intermittent sun exposure is implicated in the development of melanoma [3234]. …”
Section: Introductionmentioning
confidence: 99%
“…27,[113][114][115][116][117][118][119][120][121] The risk increases the more an individual uses indoor tanning, with younger and more frequent users having more steeply increased risk. [113][114][115][116][117][118][119][120][121] Findings consistently document a strong association between increased risk of melanoma and indoor tanning use, although the magnitude of the association varies from study to study, reflecting different populations and settings. A recent international meta-analysis that included 31 studies collectively reviewing 14,956 melanoma cases and 233,106 controls (individuals without melanoma) reported that individuals who reported ever indoor tanning had a 16% increased risk of melanoma over those who never indoor tanned.…”
Section: Indoor Tanningmentioning
confidence: 99%
“…8 In an Australian study, 95% of all melanoma cases were estimated to be due to high ambient levels of UVR exposure, when applying the same methodology as in the UK study. 9 The PAF for artificial UVR was previously estimated to be 4.6% in France 10 and 3.8% in Italy, 11 and a recent meta-analysis estimated a PAF of 5.4% in Western Europe. 12 The aim of this study was to quantify the proportion and number of melanoma cases attributable to solar UVR exposure and the use of sunbeds in France in 2015 by age and sex, and discuss the requirements for primary prevention implementation that will serve to reduce the future burden from the disease.…”
Section: Introductionmentioning
confidence: 99%
“…In an Australian study, 95% of all melanoma cases were estimated to be due to high ambient levels of UVR exposure, when applying the same methodology as in the UK study . The PAF for artificial UVR was previously estimated to be 4.6% in France and 3.8% in Italy, and a recent meta‐analysis estimated a PAF of 5.4% in Western Europe …”
Section: Introductionmentioning
confidence: 99%